(untitled) (E Conference Zone, 2022)
The purpose of the study is to develop an algorithm for the detection of dental diseases and dental care among workers of silk spinning enterprises. It was found that the incidence of the main symptoms of dental diseases among employees of Bukhara Brilliant Silk is higher than the population that does not work at the company. Of the 9 indicators identified, 8 were found to be 1.5- 7.6 times more common in workers. GVHD was 1.9 times more common among workers, stomatitis was 2.2 times more common, and candidiasis was 5.4 times more common among workers. In order to systematize and increase the efficiency of dental services, the Bukhara Brilliant Silk Silk Spinning Company has developed regulations for dental services.